2021
DOI: 10.1172/jci.insight.135623
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIB is a T cell checkpoint in antitumor immunity

Abstract: In the setting of cancer, T cells upregulate coinhibitory molecules that attenuate TCR signaling and lead to the loss of proliferative capacity and effector function. Checkpoint inhibitors currently in clinical use have dramatically improved mortality from melanoma yet are not effective in all patients, suggesting that additional pathways may contribute to suppression of tumor-specific CD8 + T cell responses in melanoma. Here, we show that FcγRIIB, an inhibitory Fc receptor previously th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
6
17
0
Order By: Relevance
“… 27 36 While naïve T cells do not express FcγRs, subsets of activated CD4+ T cells may express FcγRIIIa, FcγRIIa, and FcγRIIb, 39 40 and subsets of activated memory CD8+ T cells may express FcγRIIb. 41 CD56+ (neural cell adhesion molecule) subsets of CD3+ T cells express FcγRs and are capable of mediating ADCC, such as NK T cells expressing FcγRIIIa and γδ T cells expressing FcγRIIa and FcγRIIIa. 24 These small subsets of FcγR-expressing T cells potentially could influence the linkage between innate and adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
“… 27 36 While naïve T cells do not express FcγRs, subsets of activated CD4+ T cells may express FcγRIIIa, FcγRIIa, and FcγRIIb, 39 40 and subsets of activated memory CD8+ T cells may express FcγRIIb. 41 CD56+ (neural cell adhesion molecule) subsets of CD3+ T cells express FcγRs and are capable of mediating ADCC, such as NK T cells expressing FcγRIIIa and γδ T cells expressing FcγRIIa and FcγRIIIa. 24 These small subsets of FcγR-expressing T cells potentially could influence the linkage between innate and adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FCGR2B on malignant B-cells has been found to advance the internalization of targeting monoclonal antibodies, counteracting their capacity to generate antibody-dependent cellular cytotoxicity and thus diminishing their therapeutic efficacy [ 46 ]. Interestingly, in a melanoma mouse model, FCGR2B has been demonstrated to be upregulated in tumor-infiltrating CD8+ T-cells hampering their antitumor efficacy [ 47 ]. In the same study, it was also shown that CD8+ T-cells in melanoma patients express FCGR2B , proposing its role in down-regulating tumor-directed immune responses in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Required bound better to IgG4P was FcγRIIb/c, which may play a role in suppressing tumour-infiltrating CD8 + T cells (Farley et al, 2021). Furthermore, glycosylation profile had an impact on IgG4P ICIs-ICIs with core plant α1,3-fucose and β1,2-xylose having lower affinity to FcγRIIa, FcγRIIb/c and FcγRIIIa.…”
Section: Discussionmentioning
confidence: 99%